2010
DOI: 10.1111/j.1439-0426.2010.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the fishery of siganid juveniles caught by bagnet in Lagonoy Gulf, Southeastern Luzon, Philippines

Abstract: Summary Long‐term, excessive harvesting of juvenile fish could lead to significant decline in their settlement strength. In the Philippines, the exploitation of siganid juveniles forms an important traditional fishery but no assessment of the exploitation status of such fishery had been made. The present study is a comprehensive assessment of the siganid juvenile fishery caught by bagnet in Lagonoy Gulf (Southeastern Luzon) by analyzing the temporal trend of their catch and effort statistics. Seven species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Relatively much is known about the biology and ecology of the mottled spinefoot (e.g., Alcala et al 1979, de la Paz and Aragones 1990, Woodland 1990, although some confusion still exists in distinguishing the species from its morphologically similar sibling species, Siganus canaliculatus. Several studies of mottled spinefoot populations in the Philippines have focused on population structure, dynamics, and exploitation status toward rationalizing and proposing management schemes for catch regulation (Soliman and Yamaoka 2010) or establishment of marine reserves (Bellefleur 1997, Jumawan-Nanual andMetillo 2008).…”
Section: Genetic Structure Of Philippine Populations Of Siganus Fuscementioning
confidence: 99%
“…Relatively much is known about the biology and ecology of the mottled spinefoot (e.g., Alcala et al 1979, de la Paz and Aragones 1990, Woodland 1990, although some confusion still exists in distinguishing the species from its morphologically similar sibling species, Siganus canaliculatus. Several studies of mottled spinefoot populations in the Philippines have focused on population structure, dynamics, and exploitation status toward rationalizing and proposing management schemes for catch regulation (Soliman and Yamaoka 2010) or establishment of marine reserves (Bellefleur 1997, Jumawan-Nanual andMetillo 2008).…”
Section: Genetic Structure Of Philippine Populations Of Siganus Fuscementioning
confidence: 99%
“…Actual observations of the settlement were done by SCUBA diving in the lagoon of the island during the ‘run’ days. A unit of settlement was expressed as a ‘run’ that is the occurrence of juveniles on a given day; the number of ‘runs’ each month was positively correlated with monthly settlement volume (Soliman and Yamaoka, in press).…”
Section: Methodsmentioning
confidence: 99%
“…The tuna caught by hand‐lines were stored in ice inside styrofoam boxes for laboratory examination 3–4 h after capture. Key distinguishing mark of the spiny siganid was the dark‐brown mottled body, characteristic of the species (Soliman and Yamaoka, in press). The stage of development (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Siganus javus is an omnivore, its diet including zooplankton, such as copepods (Yuniar et al 2007), and seaweed (brown microalgae) (Noda et al 2011). In addition, the analyses of otolith microelements in a related species, Siganus fuscescens, have revealed juvenile seasonal population changes (Soliman and Yamaoka 2010); and migration to, and habitation in, river estuaries in its early life stages (Yamada and Baba 2009). A study in Mikawa bay, Japan, indicated that the adult stage of S. fuscescens tends to be inhabiting around the mouth of the bay where close to the open water; however, there was no significant spatial difference in immature stage between two different sites in shoreline (Kamohara et al 2007).…”
Section: Introductionmentioning
confidence: 99%